P3D SOFTWARE AS A RESOURCE FOR RETHINKING THE PRACTICE OF TEACHING AND LEARNING SCIENCE - Gomes, Luzivone Lopes; Moita, Filomena Maria G. da Silva Cordeiro (Seven Editora, 2026)
This article presents an excerpt from the dissertation "P3D Software as a Resource for Rethinking the Practice of Teaching and Learning Science," a research project that aimed to analyze the impact of P3D software on science education with 8th-grade students. This excerpt, of a bibliographical nature, briefly discusses teacher training and the use of digital technologies in the classroom: 3D technology, Virtual Reality (VR), also considering the presence of Artificial Intelligence (AI), which is no longer a distant reality or restricted to science fiction and is increasingly present in our lives – including in education. For science education, digital technologies can make teaching playful and awaken students' interest in learning. The theoretical framework draws on studies by Lévy (1999, 2004), Veen & Vrakking (2009), Silva (2012), Moita (2006, 2007, 2013), Amabis (2001), among others. The study revealed that the use of Virtual Reality and 3D technologies improved student participation, engagement, and performance in science classes. For students, exploring the three-dimensional (3D) environment enabled a meaningful, reflective, and ethical use of available resources. The research resulted in an interactive teaching sequence (ITS) focused on science education, using three-dimensional (3D) digital resources in pedagogical practice.DOI: https://doi.org/10.56238/sevened2026.008-029